UNPACKING MEANING-MAKING IN HYUNDAI’S 2016 SUPER BOWL AD: A MULTIMODAL TRANSITIVITY ANALYSIS - Imam Hanafi; Andri Wardana; Sopian; Rosa Kusuma Arum; Marlina Angelica Artanti (English Review: Journal of English Education, 2026)
This study addresses the following research questions: how are transitivity processes distributed across linguistic, visual, and auditory modes; how do transitivity frames construct meanings of power, control, and surveillance; and how do auditory elements interact with other modes to reinforce persuasive meaning in video commercials? Using a qualitative multimodal discourse analysis approach, the study integrates Halliday and Matthiessen’s (2014) transitivity system with Baldry and Thibault’s macro-analytical framework. The Hyundai Super Bowl 2016 commercial was segmented into 67 frames, of which 20 were selected based on camera shifts, participant interaction, product visibility, and salient multimodal features. The findings show that material processes account for 50% of the clauses (9 out of 18), positioning the car as the central Actor, while relational processes construct positive attributes associated with the product. Visual strategies, such as low-angle shots and dynamic camera movement, reinforce meanings of power and control, while auditory elements, including wolf howls, tyre screeches, and alarm sounds, contribute to themes of surveillance and protection. Persuasive meaning emerges from the coordinated interaction of semiotic modes across transitivity frames. The study extends multimodal discourse analysis by incorporating auditory resources and offers pedagogical implications for teaching students to analyse how multiple semiotic modes jointly construct meaning in media texts.